Compensating Differentials for Sexual Harassment - Hersch, Joni (American Economic Review, 2011)
Workplace sexual harassment is illegal, but many workers report that they have been sexually harassed. Exposure to the risk of sexual harassment may decrease productivity, which would reduce wages. Alternatively, workers may receive a compensating differential for exposure to sexual harassment, which would increase wages. Data on claims of sexual harassment filed with the Equal Employment Opportunity Commission are used to calculate the first measures of sexual harassment risks by industry, age group, and sex. Female workers face far higher sexual harassment risks. On balance, workers receive a compensating wage differential for exposure to the risk of sexual harassment.